Developing Information Technology in OpenCourseWare: From Movements to Opportunities in Asia - Saripudin, Saripudin; Djohar, As'Ari; Rohendi, Dedi; Abdullah, Ade Gafar (Indonesian Journal of Science and Technology, 2020)
This paper aims to summarize and analyze the Developing Information Technology in Open CourseWare (OCW) movements and new opportunities in Asia in the context of supporting the education process in higher education that is in accordance with the recent demands for graduate competency supported by IT innovation. The review method is carried out in 3 stages: searching and downloading articles, filtering and sorting, and final screening. The results of this review show that the OCW movement in Asia is growing rapidly, among others, due to IT innovation, stakeholder commitment, public awareness, and the need for quality teaching materials. In the era of web 5.0 technology, lecturers must have the competencies to develop electronic activities through the Web that make students truly active so that online learning actually takes place rather than the electronic reading process. The impact of IT innovation has brought drastic changes in the field of education in the learning process has become an effective driving tool for improving learning outcomes and achieving educational goals, one of the most recent innovations is OCW. OCW movement in Asia has progressed rapidly and significantly, although they experience transformations in accordance with technological developments and needs in the field.